Contribución del quimismo del agua de lluvia, de la deposición seca y la lixiviación, sobre la química de los flujos de trascolación y escorrentía cortical en el encinar mediterráneo - Bellot J.; Escarré A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
This study shows the most important chemical characteristics of throughfall and stemflow in three species of Mediterranean holm-oak forest (Quercus ilex, Arbutus unedo y Phillyrea media), as well as their relationship with rainfall water chemistry and dry deposition. At the same time, it compares 3 models to evaluate the importance and amount of wet and dry deposition, as well as of leaching, in nutrients present in throughfall and stemflow.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)